FINANCIAL AND ECONOMIC STABILITY AS CONDITION FOR THE FORMATION OF THE POTENTIAL FOR THE DEVELOPMENT OF DOMESTIC INNOVATIVE BUSINESS IN THE CONDITIONS OF WAR - BILYK, Victoria (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the study, the focus of attention is focused on the problems of the state policy of stimulating the development of innovative entrepreneurship. On the one hand, innovative business develops under the condition of sufficient financial and resource support, and, therefore, good business results; however, on the other hand, innovative activity is a factor in the strength of positions and stability of business entities in the complex socio-economic conditions of the crisis. It is from such positions that the purpose of the study is to justify the tools and means of the state policy of strengthening financial and economic stability in the context of the formation and realization of the potential for the development of innovative business in Ukraine in the conditions of war. The substantive characteristics and basic tools of the policy of ensuring the financial and economic stability of the entrepreneurial sector of the national economy are summarized. A system of measures and tools of the state policy toolkit of strengthening financial and economic stability has been developed to stimulate the development of domestic innovative business, namely in the areas of: attracting opportunities of the financial and credit system; strengthening of financial and investment cooperation of business; stimulating the restoration of efficiency and improvement of the financial and economic condition of business entities; support for measures to develop the business activity of business entities. The implementation of state policy in these areas will allow: to improve the financial support of business entities, to improve the management of innovative development and to increase process innovations; attract external financial and resource support for innovative purposes; to improve internal capabilities for the activation of innovative activities, the introduction of product innovations; increase the economic efficiency of the business, increase the scale of operations and improve the opportunities for financing organizational and marketing innovations